Optimization of heat transfer on thermal barrier coated gas turbine blade - Aabid, Abdul; Khan, Sher Afghan (Institute of Physics Publishing, 2018)
In the field of Aerospace Propulsion technology, material required to resist the maximum temperature. In this paper, using thermal barrier coatings (TBCs) method in gas turbine blade is used to protect hot section component from high-temperature effect to extend the service life and reduce the maintenance costs. The TBCs which include three layers of coating corresponding initial coat is super alloy-INCONEL 718 with 1 mm thickness, bond coat is Nano-structured ceramic-metallic composite-NiCoCrAIY with 0.15 mm thickness and top coat is ceramic composite-La2Ce2O7 with 0.09 mm thickness on the nickel alloy turbine blade which in turn increases the strength, efficiency and life span of the blades. Modeling a gas turbine blade using CATIA software and determining the amount of heat transfer on thermal barrier coated blade using ANSYS software has been performed. Thermal stresses and effects of different TBCs blade base alloys are considered using CATIA and ANSYS.